This girl is different - Johnson, J. J., 1973- (Atlanta, Ga. : Peachtree, 2011)
Having always been home schooled by her counter-culture mother, Evie has decided to spend her senior at the local public high school, an experience that challenges her preconceptions about friendship, boundaries, and power.
The word "different" is written upside down and backwards on t.p.
012-016.
Keywords: High schools -- Juvenile fiction; Schools -- Juvenile fiction; Hippies -- Juvenile fiction; Individuality -- Juvenile fiction; Interpersonal relations -- Juvenile fiction